High-fiber-diet-related metabolites improve neurodegenerative symptoms in patients with obesity with diabetes mellitus by modulating the hippocampal–hypothalamic endocrine axis - Luo, Ning; Guo, Yuejie; Peng, Lihua; Deng, Fangli (Frontiers in Neurology, 2023)
OBJECTIVE: Through single-gene transcriptomic and metabolomic analyses, this study examined the role of high-fibre diet in obesity complicated by diabetes and neurodegenerative symptoms. METHOD: The expression matrix of high-fibre-diet-related metabolites, blood methylation profile associated with pre-symptomatic dementia in elderly patients with type 2 diabetes mellitus (T2DM), and high-throughput single-cell sequencing data of hippocampal samples from patients with Alzheimer's disease (AD) were retrieved from the Gene Expression Omnibus (GEO) database and through a literature search. Data were analyzed using principal component analysis (PCA) after quality control and data filtering to identify different cell clusters and candidate markers. A protein–protein interaction network was mapped using the STRING database. To further investigate the interaction among high-fibre-diet-related metabolites, methylation-related DEGs related to T2DM, and single-cell marker genes related to AD, AutoDock was used for semi-flexible molecular docking. RESULT: Based on GEO database data and previous studies, 24 marker genes associated with high-fibre diet, T2DM, and AD were identified. Top 10 core genes include SYNE1, ANK2, SPEG, PDZD2, KALRN, PTPRM, PTPRK, BIN1, DOCK9 and NPNT, and their functions are primarily related to autophagy. According to molecular docking analysis, acetamidobenzoic acid, the most substantially altered metabolic marker associated with a high-fiber diet, had the strongest binding affinity for SPEG. CONCLUSION: By targeting the SPEG protein in the hippocampus, acetamidobenzoic acid, a metabolite associated with high-fibre diet, may improve diabetic and neurodegenerative diseases in obese people.